The Unbounded Space and Moral Transgression: Capitalist Expansion in West New Britain. Issue 1 (2nd January 2018) - Guinness, Patrick
ABSTRACT: Capitalist transformations in West New Britain Province, Papua New Guinea, have focused on setting boundaries on land and social relations as an efficient way to generate productive relations. But for the Maututu around Bialla town where the palm oil industry has been established the perception of productivity rests not on establishing boundaries but on exploring horizons. Recent dramatic changes to the economy and demography of this area have introduced moral conflict into Maututu endeavours to generate well-being. Maututu have responded to these conflicts in ways that continue to bring their indigenous morality to bear on the moral strategies pursued by state and capitalist forces.